ISSUES OF INTERNATIONAL COOPERATION IN THE FIGHT AGAINST DRUG-RELATED CRIMES - Urazaliev Murad Karaevich (International Journal of Business, Law and Political Science, 2024)
The article presents views on the prospects for improving international cooperation in the fight against drug addiction, problems of drug use and psychotropic substances and their negative consequences. Also, an analysis of international legal acts on combating drug addiction is given